Influence of variables related to soil weathering on the geomechanical performance of tropical soils - Pierozan, Rodrigo Cesar (2023)
This paper presents an experimental and analytical investigation of the influence of variables related to soil weathering on the geomechanical performance of sand-silt mixtures containing lateritic soils, i.e. intensely weathered tropical soils with the influence of interparticle bonding. The sand-silt mixtures containing different relative proportions between uniform sand and lateritic soil were produced, and geomechanical soil characterization tests were performed. Based on the results, a transition from a primarily coarse-to a fine-grained prevailing soil structure was found to cause considerable impact on the geomechanical performance of these soils, as evidenced by design variables related to soil mineralogy and size distribution characteristics. Specifically, fines contents of both individual soil particles and soil aggregations were found to correlate with experimental results, while the relative proportion between sesquioxides (aluminum, and iron oxides), and silica, i.e. sesquioxide-silica ratios (SSR−1), facilitated estimates concerning changes in geomechanical performance. Finally, the application of the sand-silt mixtures containing lateritic soil on soil walls reinforced with polymeric strips was also evaluated, further emphasizing the potential advantages of adopting variables related to soil weathering on design guidelines concerning tropical soils.